Carrier film and reinforced film with carrier film

CN122956826APending Publication Date: 2026-10-23NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610507726.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-17
Filing Date
2026-04-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]再者,当使用具备抗静电层的载体膜时,存在拾取胶带的拾取性降低、无法顺畅地从加强膜剥离载体膜的问题

Benefits of technology

根据本发明,能够提供一种具有抗静电层的载体膜,所述载体膜的拾取性优异。此外,能够提供一种具有这样的载体膜的带载体膜的加强膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956826A_ABST
    Figure CN122956826A_ABST
Patent Text Reader

Abstract

The present application relates to a carrier film and a carrier film-strengthened film. The present application provides a carrier film having an antistatic layer, the carrier film being excellent in pick-up property. Further, the present application provides a carrier film-strengthened film having such a carrier film. The carrier film of an embodiment of the present application successively has an antistatic layer, a substrate, and an adhesive layer, the antistatic layer being formed from an antistatic layer-forming composition containing a binder and an antistatic agent, the antistatic layer-forming composition containing a water-based polyurethane resin (A) having at least one selected from the group consisting of an ether structure and an ester structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to carrier membranes and reinforcing membranes with carrier membranes. Background Technology

[0002] In the manufacture of optical devices, electronic devices, etc., in order to give the optical components, electronic components, etc. rigidity and impact resistance, a reinforcing film (typically a reinforcing substrate with an adhesive layer) is pre-attached to the exposed side of the optical component, electronic component, etc. for reinforcement (Patent Document 1).

[0003] In the case of such reinforcing films, a carrier film having a substrate and an adhesive layer is laminated to the substrate side of the reinforcing film for transport during the manufacture of optical devices, electronic devices, etc., and to prevent surface damage. 。 Such a carrier film is peeled off from the reinforcing film at a point when it is no longer needed for transport or to prevent surface damage. Peeling such a carrier film usually involves attaching a pickup tape to the back side of the carrier film (the outermost surface side opposite to the reinforcing film), picking it up, and then peeling it off.

[0004] Regarding carrier films, for antistatic purposes, an antistatic layer formed from an antistatic layer forming composition comprising an adhesive and an antistatic agent is sometimes provided on the back side of the substrate (the side opposite to the adhesive layer). As such an antistatic layer, for example, an antistatic layer formed from a specific antistatic agent composition comprising a conductive polymer component and an adhesive has been reported (Patent Document 2).

[0005] Furthermore, when using a carrier film with an antistatic layer, there are problems such as reduced pick-up of the pick-up tape and difficulty in smoothly peeling the carrier film off the reinforcing film.

[0006] Existing technical documents Patent documents Patent Document 1: Japanese Patent No. 7570928 Patent Document 2: Japanese Patent No. 6742723 Summary of the Invention

[0007] The technical problem of this invention is to provide a carrier film with an antistatic layer, which has excellent pick-up properties. Furthermore, the technical problem of this invention is to provide a reinforced film with such a carrier film.

[0008] To solve the aforementioned technical problems, the inventors conducted research. The results showed that when an aqueous polyurethane resin having a specific structure is added to an antistatic layer forming composition, specifically an aqueous polyurethane resin having at least one structure selected from the group consisting of ether and ester structures, the pick-up capability is significantly improved.

[0009] [1] The carrier film of the present invention sequentially comprises an antistatic layer, a substrate and an adhesive layer, the antistatic layer being formed by an antistatic layer forming composition comprising an adhesive and an antistatic agent, the antistatic layer forming composition comprising an aqueous polyurethane resin (A), the aqueous polyurethane resin (A) having at least one selected from the group consisting of an ether structure and an ester structure.

[0010] [2] Alternatively, in the carrier film described in [1] above, the content of the aqueous polyurethane resin (A) in the antistatic layer forming composition is 1 to 50 parts by weight relative to a total of 100 parts by weight of the binder and the antistatic agent, calculated based on the solid content.

[0011] [3] Alternatively, in the carrier film described in [1] or [2] above, the binder is polyester resin.

[0012] [4] Alternatively, in any one of the carrier films described in [1] to [3] above, the antistatic agent is a conductive polymer.

[0013] [5] The reinforcing film with a carrier film in the embodiments of the present invention has a reinforcing film on the adhesive layer side of the carrier film as described in any one of [1] to [4] above.

[0014] Invention Effects According to the present invention, a carrier film having an antistatic layer can be provided, the carrier film having excellent pick-up properties. Furthermore, a reinforced film with such a carrier film can be provided. Attached Figure Description

[0015] Figure 1 This is a schematic cross-sectional view of a carrier membrane according to one embodiment of the present invention.

[0016] Figure 2 This is a schematic cross-sectional view of a reinforced membrane with a carrier membrane according to one embodiment of the present invention. Detailed Implementation

[0017] In the presence of the term "weight" in this specification, it may be replaced with "mass," which is commonly used as a SI unit for expressing weight.

[0018] In this specification, the term "(meth)acrylic acid" refers to "acrylic acid and / or methacrylic acid"; the term "(meth)acrylate" refers to "acrylate and / or methacrylate"; the term "(meth)allyl" refers to "allyl and / or methylallyl"; and the term "(meth)acrolein" refers to "acrolein and / or methacrolein". The term "alkyl" in this specification also includes cycloalkyl (e.g., cyclopentyl, cyclohexyl). Furthermore, the term "alkyl" in this specification can refer to either straight-chain alkyl or branched-chain alkyl.

[0019] 1. Carrier Membrane The carrier film of the embodiments of the present invention is a carrier film having an antistatic layer, a substrate, and an adhesive layer in sequence. The carrier film of the embodiments of the present invention, as long as it has an antistatic layer, a substrate, and an adhesive layer in sequence, can have any other suitable layers without impairing the effects of the present invention. The aforementioned antistatic layer is representatively the outermost layer.

[0020] In the carrier film of an embodiment of the present invention, a release liner may be provided on the exposed side of the adhesive layer (the side opposite to the substrate) until use. For example, when the carrier film of an embodiment of the present invention is bonded to a reinforcing film, the adhesive layer exposed by peeling off the release liner is bonded to the reinforcing film.

[0021] Figure 1 This is a schematic cross-sectional view of a carrier membrane according to one embodiment of the present invention. Figure 1 In this process, the carrier film 1000 is composed of an antistatic layer 100, a substrate 200, and an adhesive layer 300.

[0022] The overall thickness of the carrier membrane in the embodiments of the present invention is, for example, 7 μm to 500 μm, 13 μm to 250 μm, 20 μm to 200 μm, or 27 μm to 150 μm.

[0023] From the viewpoint of exhibiting excellent antistatic properties, the surface resistivity of the carrier film in the embodiment of the present invention, as measured on the surface of the antistatic layer, is preferably less than 1.0 × 10⁻⁶. 11 Ω can also be less than 1.0 × 10 10 Ω can also be less than 1.0 × 10 9 Ω can also be less than 1.0 × 10 8 Ω can also be less than 1.0 × 10 7 Ω can also be less than 1.0 × 10 6 Ω. The method for determining the surface resistivity will be described in detail later.

[0024] 1-1. Antistatic Layer The antistatic layer is formed from an antistatic layer forming composition comprising an adhesive and an antistatic agent. The antistatic layer can typically be formed by applying the antistatic layer forming composition to a substrate and allowing it to dry or cure. Examples of application methods include roller coating, bar coating, and gravure coating.

[0025] The thickness of the antistatic layer can be, for example, 3nm to 500nm, 3nm to 100nm, or 3nm to 60nm. If the thickness of the antistatic layer is too small, it will be difficult to form the antistatic layer uniformly (for example, the thickness deviation caused by position in the antistatic layer will become larger), and therefore, the appearance of the surface protective film may be uneven. If the thickness of the antistatic layer is too large, it may affect the overall properties of the carrier film.

[0026] The antistatic layer forming composition comprises an aqueous polyurethane resin (A) having at least one structure selected from the group consisting of an ether structure and an ester structure. By comprising an aqueous polyurethane resin (A) having such a specific structure in the antistatic layer forming composition, the effects of the present invention can be achieved, and a carrier film with excellent pick-up properties can be provided.

[0027] <1-1-a. Adhesive> The composition for forming an antistatic layer includes an adhesive. By including an adhesive in the composition for forming an antistatic layer, the antistatic layer can be endowed with solvent resistance, mechanical strength, thermal stability, etc. The adhesive may be a single type or two or more types.

[0028] As a binder, any suitable resin may be used without impairing the effects of the present invention. Examples of such resins include: polyester resin, acrylic resin, polyethylene resin, urethane acrylate resin, styrene acrylate resin, silicone acrylate resin, silicone resin, fluororesin, styrene resin, alkyd resin, melamine resin, epoxy resin, polyurethane resin, amide resin, polyolefin resin, and polysilazane resin.

[0029] As an adhesive, polyester resin is preferred from the viewpoints of excellent solvent resistance and the ability to suppress edge shrinkage during film formation due to its low surface free energy. The content of polyester resin in the adhesive is preferably 50% to 100% by weight, but can be 70% to 100% by weight, 90% to 100% by weight, 95% to 100% by weight, 98% to 100% by weight, or substantially 100% by weight.

[0030] The polyester resin preferably has a structure formed by the condensation of at least one compound (polycarboxylic acid component) selected from polycarboxylic acids (typically dicarboxylic acids) and their derivatives (anhydrides, esters, halides, etc. of polycarboxylic acids) having two or more carboxyl groups in one molecule and at least one compound (polyol component) selected from polyols (typically diols) having two or more hydroxyl groups in one molecule.

[0031] Examples of compounds that can be used as polycarboxylic acid components include: oxalic acid, malonic acid, difluoromalonic acid, alkylmalonic acid, succinic acid, tetrafluorosuccinic acid, alkylsuccinic acid, (±)-malic acid, meso-tartaric acid, itaconic acid, maleic acid, methylmaleic acid, fumaric acid, methylfumaric acid, acetylenic acid, glutaric acid, hexafluoroglutaric acid, methylglutaric acid, pentenic acid, adipic acid, dithioadipic acid, methyl adipic acid, dimethyl adipic acid, tetramethyl adipic acid, methylene adipic acid, mucoconic acid, galactosic acid, pimelic acid, octanoic acid, perfluorooctanoic acid, 3,3,6,6-tetramethyloctanoic acid, azelaic acid, sebacic acid, perfluorosebacic acid, tridecanoic acid, dodecyl dicarboxylic acid, tridecyl dicarboxylic acid, tetradecyl dicarboxylic acid, and other aliphatic dicarboxylic acids; cycloalkyl dicarboxylic acids (e.g., 1,4-cyclohexanedicarboxylic acid). Carboxylic acids, including 1,2-cyclohexanedicarboxylic acid, 1,4-(2-norbornene)dicarboxylic acid, 5-norbornene-2,3-dicarboxylic acid (nadic acid), adamantanedicarboxylic acid, spiroheptanedicarboxylic acid, and other alicyclic dicarboxylic acids; phthalic acid, isophthalic acid, dithioisophthalic acid, methylisophthalic acid, dimethylisophthalic acid, chloroisophthalic acid, dichloroisophthalic acid, terephthalic acid, methylterephthalic acid, dimethylterephthalic acid, chloroterephthalic acid, bromoterephthalic acid, naphthalenedicarboxylic acid, fluorenonedicarboxylic acid, anthracenedicarboxylic acid, biphenyldicarboxylic acid, biphenylenedicarboxylic acid, dimethyl biphenylenedicarboxylic acid, 4,4”-p-terphenylenedicarboxylic acid, 4,4”-p-tetraphenyldicarboxylic acid, bibenzyldicarboxylic acid, azobenzyldicarboxylic acid, and homophthalic acid. Aromatic dicarboxylic acids such as phenylene diacetic acid, phenylene dipropionic acid, naphthalene dicarboxylic acid, biphenyl diacetic acid, 3,3'-[4,4'-(methylene di-p-phenylene)] dipropionic acid, 4,4'-bibenzyl diacetic acid, 3,3'(4,4'-bibenzyl) dipropionic acid, and oxydi-p-phenylene diacetic acid; anhydrides of any of the above polycarboxylic acids; esters of any of the above polycarboxylic acids (e.g., alkyl esters, monoesters, diesters, etc.); and acyl halides (e.g., dicarboxyl chlorides) corresponding to any of the above polycarboxylic acids.

[0032] Preferred compounds that can be used as polycarboxylic acid components include: aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and naphthalene dicarboxylic acid and their anhydrides; aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, succinic acid, fumaric acid, maleic acid, nadic acid, and 1,4-cyclohexane dicarboxylic acid and their anhydrides; and lower alkyl esters of said dicarboxylic acids (e.g., esters with monohydric alcohols having 1 to 3 carbon atoms).

[0033] Examples of compounds that can be used as polyol components include: ethylene glycol, propylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 3-methylpentanediol, diethylene glycol, 1,4-cyclohexanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, benzenediol, hydrogenated bisphenol A, bisphenol A, and other diols. Other examples include alkylene oxide adducts of these compounds (e.g., ethylene oxide adducts, propylene oxide adducts, etc.).

[0034] From the perspective of further demonstrating the effects of the present invention, the molecular weight of the polyester resin is expressed as the weight-average molecular weight Mw converted from standard polystyrene by gel permeation chromatography (GPC), for example, 5 × 10⁻⁶. 3 ~1.5×10 5 It can also be 1×10 4 ~6×10 4 .

[0035] From the perspective of further demonstrating the effects of the present invention, the glass transition temperature Tg of the polyester resin is preferably 0℃~120℃, or it can be 10℃~80℃.

[0036] Commercially available products can be used as polyester resins. Examples of such commercially available products include: Toyobo Co., Ltd.'s products under the brand names "VYLONAL MD-1100", "VYLONAL MD-1200", "VYLONAL MD-1245", "VYLONAL MD-1335", "VYLONAL MD-1480", "VYLONAL MD-1500", "VYLONAL MD-1930", "VYLONAL MD-1985", and "VYLONAL MD-2000"; and Koei Chemical Industry Co., Ltd.'s products under the brand names "PLAS COAT Z-221", "PLAS COAT Z-446", "PLAS COAT Z-561", "PLAS COAT Z-565", "PLAS COAT Z-880", "PLAS COAT Z-3310", "PLAS COAT RZ-105", "PLAS COAT RZ-570", and "PLAS COAT Z-730". Z-760", "PLAS COAT Z-592", "PLAS COAT Z-687", "PLAS COAT Z-690"; trade names of "PESRESIN A-110", "PESRESIN A-120", "PESRESIN A-124GP", "PESRESIN A-125S", "PESRESIN" manufactured by Takamatsu Oil and Oil Co., Ltd. A-160P", "PESRESIN A-520", "PESRESIN A-613D", "PESRESIN A-615GE", "PESRESIN A-640", "PESRESIN A-645GH", "PESRESIN A-647GEX", "PESRESIN A-680", "PESRESIN A-684G", "PESRESIN WAC-14", "PESRESINWAC-17XC".

[0037] <1-1-b. Antistatic Agent> The composition for forming an antistatic layer includes an antistatic agent. By including an antistatic agent in the composition for forming an antistatic layer, the antistatic layer can be imparted with an antistatic effect. The antistatic agent may be one type or two or more types.

[0038] The proportion of antistatic agent in the composition for forming the antistatic layer, calculated based on solid components, is, for example, 10 to 200 parts by weight, 25 to 150 parts by weight, or 30 to 120 parts by weight relative to 100 parts by weight of the adhesive.

[0039] As an antistatic agent, any suitable antistatic agent can be used without impairing the effects of the present invention. Examples of such antistatic agents include conductive polymers, carbon nanotubes, and ion-conducting polymers, with conductive polymers being preferred. There may be only one type of conductive polymer, or there may be two or more types.

[0040] As a conductive polymer, any suitable conductive polymer can be used without impairing the effects of the present invention. Examples of such conductive polymers include water-soluble conductive polymers and water-dispersible conductive polymers.

[0041] Examples of water-soluble conductive polymers include polyaniline sulfonic acid, poly(isothioindene dimethyl sulfonate) compounds, and (meth)acrylate polymers containing quaternary ammonium salts, with polyaniline sulfonic acid being the most preferred.

[0042] Examples of water-dispersible conductive polymers include polythiophene and polyaniline doped with polyanionic polymers, with polythiophene doped with polyanionic polymers being preferred.

[0043] Examples of polythiophenes that can be used as water-dispersible conductive polymers include: polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), and poly(3- Chlorothiophene), poly(3-iodothiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptoxythiophene), poly(3-octoxythiophene), poly(3-decoxythiophene), poly(3-... - Dodecyloxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly( Poly(3,4-bis(dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butadienedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), poly(3-methyl-4-carboxybutylthiophene). The degree of polymerization of polythiophenes is, for example, 2 to 1000, or 5 to 100.

[0044] As a water-dispersible conductive polymer, poly(3,4-ethylenedioxythiophene) (PEDOT) is preferred in terms of further demonstrating the effects of the present invention.

[0045] Polyanionic polymers are polymers with anionic structural units that function as dopants for polythiophenes. Examples of polyanionic polymers include: polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly(2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polysulfonyl methacrylate, poly(4-sulfobutyl methacrylate), polymethallyloxybenzene sulfonic acid, polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid carboxylic acid, polymethacrylic acid carboxylic acid, poly(2-acrylamide-2-methylpropane carboxylic acid), polyisoprene carboxylic acid, polyacrylic acid, and polysulfonated phenylacetylene. Polyanionic polymers can be homopolymers of these polymers or copolymers of two or more polymers. For optimal doping and dispersibility with polythiophenes, the weight-average molecular weight (Mw) of the polyanionic polymer is preferably 10 million to 1 million, but can also be 20 million to 500,000.

[0046] As a polyanionic acid, polystyrene sulfonic acid (PSS) is preferred.

[0047] As a conductive polymer, for example, when poly(3,4-ethylenedioxythiophene) (PEDOT) is used as a polythiophene and polystyrene sulfonic acid (PSS) is used as a polyanionic polymer that can dope polythiophene, PEDOT and PSS interact and exist at very close range. As a result, electrons of PEDOT are taken away by PSS, which can endow the antistatic layer with excellent antistatic properties.

[0048] Commercially available polythiophene products doped with polyanionic compounds include, for example, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid (PEDOT / PSS) manufactured by HCStark under the trade name "Bytron P", manufactured by Shin EtsuPolymer under the trade name "SEPLEGYDA", and manufactured by Soken Chemical under the trade name "VERAZOL".

[0049] The weight-average molecular weight (Mw) of polyaniline sulfonic acid, which can be used as a component of water-soluble conductive polymers, is, for example, 1 × 10⁻⁶. 3 ~5×10 5 It can also be 5×10 3 ~3×10 5 .

[0050] Commercially available products of polyaniline sulfonic acid include, for example, the product "aquaPASS" manufactured by MITSUBISHI RAYON.

[0051] <1-1-c. Aqueous polyurethane resin (A)> The antistatic layer forming composition comprises an aqueous polyurethane resin (A) having at least one structure selected from the group consisting of an ether structure and an ester structure. By comprising an aqueous polyurethane resin (A) having such a specific structure in the antistatic layer forming composition, the effects of the present invention can be achieved, and a carrier film with excellent pick-up properties can be provided.

[0052] As an aqueous polyurethane resin (A) having at least one of the groups selected from ether structure and ester structure, specifically, it is any one of aqueous polyurethane resin having ether structure, aqueous polyurethane resin having ester structure, and aqueous polyurethane resin having both ether structure and ester structure.

[0053] Aqueous polyurethane resins can be provided, for example, in the form of aqueous dispersions, and can be hydrophilic polyurethane resins.

[0054] Polyurethane resins are typically manufactured through the reaction of polyols with isocyanate compounds. Commonly known polyols used in this reaction include polyether polyols, polyester polyols, and polycarbonate polyols. Polyurethane resins manufactured using polyether polyols are called ether-based polyurethane resins and have an ether structure. Polyurethane resins manufactured using polyester polyols are called ester-based polyurethane resins and have an ester structure. Polyurethane resins manufactured using both polyether polyols and polyester polyols are called ether / ester-based polyurethane resins and have both ether and ester structures. Polyurethane resins manufactured using polycarbonate polyols are called carbonate-based polyurethane resins and have a carbonate structure.

[0055] Since the aqueous polyurethane resin (A) is an aqueous polyurethane resin having at least one structure selected from the group consisting of an ether structure and an ester structure, it is specifically equivalent to an aqueous ether-based polyurethane resin, an aqueous ester-based polyurethane resin, or an aqueous ether / ester-based polyurethane resin. From the viewpoints of availability and cost, an aqueous ether-based polyurethane resin or an aqueous ester-based polyurethane resin is preferred as the aqueous polyurethane resin (A).

[0056] As for water-based ether-based polyurethane resins, commercially available products can be used, such as: "TAKELAC W-5661", "TAKELAC W-6020", "TAKELAC W-6061", "TAKELAC WS-6021", and "TAKELAC WSA-5920" manufactured by Mitsui Chemicals Co., Ltd.; and "SUPERFLEX SF-130", "SUPERFLEX SF-870", and "SUPERFLEX SFE-4800" manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.

[0057] As for water-based ester-based polyurethane resins, commercially available products can be used, such as: "TAKELAC W-5030", "TAKELAC W-5335", "TAKELAC W-405", "TAKELAC W-605", "TAKELAC WS-4022", "TAKELAC WS-5000", and "TAKELAC WS-5984" manufactured by Mitsui Chemicals Co., Ltd.; and "SUPERFLEX SF-210", "SUPERFLEX SF-500M", "SUPERFLEX SF-620", "SUPERFLEX SF-740", "SUPERFLEX SF-820", "SUPERFLEX SF-830HS", "SUPERFLEX SF-860", and "SUPERFLEX SFE-2000" manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.

[0058] The proportion of aqueous polyurethane resin (A) having at least one of the group consisting of ether and ester structures in the antistatic layer forming composition, calculated based on solid content, is preferably 1 to 50 parts by weight relative to 100 parts by weight of the total binder and antistatic agent. It can be 5 to 40 parts by weight, 5 to 35 parts by weight, 10 to 30 parts by weight, 10 to 25 parts by weight, or 10 to 20 parts by weight. If the proportion of aqueous polyurethane resin (A) in the antistatic layer forming composition is too low, the effects of the present invention may not be achieved. If the proportion of aqueous polyurethane resin (A) in the antistatic layer forming composition is too high, the antistatic effect may be reduced, and defects such as edge shrinkage may occur during the formation of the antistatic layer.

[0059] From the viewpoint of further demonstrating the effects of the present invention, the lower the proportion of aqueous polyurethane resin (A) in the composition for forming the antistatic layer, excluding aqueous polyurethane resin (A) having at least one of the groups selected from ether and ester structures, the better. In terms of solid content, it is preferably less than 50 parts by weight relative to 100 parts by weight of the total binder and antistatic agent, and can be less than 30 parts by weight, less than 20 parts by weight, less than 10 parts by weight, less than 5 parts by weight, less than 1 part by weight, less than 0.1 parts by weight, or less than 0.01 parts by weight.

[0060] <1-1-d. Crosslinking agent> The composition for forming the antistatic layer may contain a crosslinking agent. There may be only one type of crosslinking agent, or there may be two or more types.

[0061] The proportion of the crosslinking agent in the composition for forming the antistatic layer, calculated based on the solid components, is, for example, less than 100 parts by weight relative to the total of the binder and the antistatic agent. It can be 1 to 100 parts by weight, 5 to 80 parts by weight, 5 to 60 parts by weight, 5 to 40 parts by weight, or 10 to 30 parts by weight.

[0062] Examples of crosslinking agents include silane coupling agents, epoxy crosslinking agents, melamine crosslinking agents, and isocyanate crosslinking agents, with melamine crosslinking agents and isocyanate crosslinking agents being preferred.

[0063] Examples of melamine-based crosslinking agents include: melamine, alkylated melamine, alkoxylated alkylated melamine, hydroxymethyl melamine, and alkoxylated hydroxymethyl melamine.

[0064] Examples of isocyanate-based crosslinking agents include those that are stable in aqueous solutions. Examples of isocyanate-based crosslinking agents include substances formed by capping the isocyanate-based crosslinking agent with alcohols, phenols, thiophenols, amines, imides, oximes, lactams, active methylene compounds, thiols, imides, ureas, diaryl compounds, sodium bisulfite, etc.

[0065] <1-1-e. Solvent> The composition for forming the antistatic layer may contain a solvent. There may be only one solvent or two or more solvents.

[0066] Without impairing the effects of the present invention, the solvent content in the composition for forming the antistatic layer can be any appropriate proportion depending on other components, purpose, operability, etc.

[0067] Solvents include organic solvents, water, or mixtures thereof. A solvent may be a single solvent or two or more. Examples of organic solvents include: esters such as ethyl acetate; ketones such as methyl ethyl ketone, acetone, and cyclohexanone; cyclic ethers such as tetrahydrofuran (THF) and dioxane; aliphatic or alicyclic hydrocarbons such as n-hexane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; aliphatic or alicyclic alcohols such as methanol, ethanol, n-propanol, isopropanol, and cyclohexanol; and glycol ethers such as alkylene glycol monoalkyl ethers (e.g., ethylene glycol monomethyl ether and ethylene glycol monoethyl ether) and diallyl glycol monoalkyl ethers.

[0068] As a solvent, a mixture of organic solvent and water is preferred, a mixture of aliphatic or alicyclic alcohol and water is more preferred, and a mixture of aliphatic alcohol and water is even more preferred.

[0069] <1-1-f. Other components> The composition for forming the antistatic layer may contain other components as needed. These other components may be only one or more.

[0070] Without impairing the effects of the present invention, the proportions of other components in the composition for forming the antistatic layer can be any suitable proportion. Such proportions, converted to solids content, are, for example, 0 to 50 parts by weight relative to a total of 100 parts by weight of the binder and antistatic agent, 0 to 30 parts by weight, 0 to 10 parts by weight, 0 to 5 parts by weight, or 0 to 1 part by weight.

[0071] Other components include, for example: lubricants, antioxidants, colorants (pigments, dyes, etc.), flow modifiers (thixotropic agents, thickeners, etc.), dispersants, film-forming aids, surfactants (defoamers, etc.), preservatives, and conductivity improvers (glycidyl compounds, polar solvents, polyaliphatic alcohols, lactam compounds, etc.).

[0072] 1-2. Substrate The substrate can be a single layer or two or more layers. Typically, the substrate is a single layer.

[0073] The thickness of the substrate can be, for example, 1μm to 500μm, 5μm to 300μm, 10μm to 150μm, 15μm to 100μm, 20μm to 90μm, or 25μm to 80μm.

[0074] The substrate material can be any suitable material without impairing the effects of the present invention. Examples of such materials include resin materials, paper, and nonwoven fabrics, with resin materials being preferred. The substrate can be composed of one material or two or more materials. For example, the substrate can be composed of two or more plastics.

[0075] Resin materials used as base materials include, for example: polyimide (PI), polyetheretherketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polymethyl methacrylate (PMMA) and other acrylic resins, polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), fully aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorinated resins, and cyclic olefin polymers.

[0076] The substrate may contain any appropriate additives as needed. Examples of additives that may be contained in the substrate (1) include: antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fillers, and pigments. The types, quantities, and amounts of additives that may be contained in the substrate may be appropriately determined according to the purpose.

[0077] 1-3. Adhesive Layer The adhesive layer can be one layer or two or more layers.

[0078] The adhesive force of the adhesive layer constituting the carrier film can be set to any suitable adhesive force according to the purpose. Considering that a reinforcing film with a carrier film is formed by bonding it to a reinforcing film, the adhesive force of the adhesive layer constituting the carrier film is preferably less than the adhesive force of the adhesive layer constituting the reinforcing film.

[0079] As the adhesive layer, an adhesive layer composed of any suitable adhesive may be used without impairing the effects of the present invention. Examples of adhesives constituting the adhesive layer include acrylic adhesives, urethane adhesives, rubber adhesives, and silicone adhesives. As acrylic adhesives, urethane adhesives, rubber adhesives, and silicone adhesives, they may be appropriately selected from various conventionally known adhesives without impairing the effects of the present invention.

[0080] As a representative example of adhesives, acrylic adhesives will be described.

[0081] Acrylic adhesives are formed from acrylic adhesive composition (A). Acrylic adhesives can be formed by crosslinking reactions of acrylic adhesive composition (A) due to heating, ultraviolet irradiation, etc.

[0082] When the acrylic adhesive is formed from the acrylic adhesive composition (A), any suitable method can be used to form the acrylic adhesive without impairing the effects of the present invention. Examples of such methods for forming the acrylic adhesive include: applying the acrylic adhesive composition (A) to any suitable substrate, heating and drying it as needed, and curing it as needed to form the acrylic adhesive on the substrate; or applying the acrylic adhesive composition (A) to any suitable release liner or other film, heating and drying it as needed, and curing it as needed to form the acrylic adhesive on the film, and then transferring it onto any suitable substrate to form the acrylic adhesive on the substrate. Any suitable method can be used as such a coating method without impairing the effects of the present invention. Examples of such coating methods include: roller coating, gravure roller coating, reverse roller coating, licking coating, dip roller coating, bar coating, brush coating, spraying, doctor blade coating, air knife coating, comma coating, direct coating, and mold coating. The heating and drying of the acrylic adhesive composition (A) can be performed by any suitable method without impairing the effects of the present invention. Examples of such heating and drying methods include heating to 60°C to 180°C. The curing of the acrylic adhesive composition (A) can be performed by any suitable method without impairing the effects of the present invention. Examples of such curing methods include: heat, ultraviolet radiation, laser irradiation, alpha irradiation, beta irradiation, gamma irradiation, X-ray irradiation, and electron beam irradiation.

[0083] <1-3-a. Acrylic polymers (A)> The acrylic adhesive composition (A) comprises an acrylic polymer (A) as a base polymer. The acrylic polymer (A) may be one or more.

[0084] The proportion of acrylic polymer (A) in the acrylic adhesive composition (A) can be any suitable proportion without impairing the effects of the present invention. For example, the proportion of acrylic polymer (A) in the acrylic adhesive composition (A) is 50% by weight or more, or it can be 60% to 99.9% by weight, 70% to 99% by weight, 80% to 98% by weight, or 90% to 97% by weight.

[0085] The weight-average molecular weight (Mw) of the acrylic polymer (A) is preferably above 100,000, but can be between 100,000 and 5,000,000, between 200,000 and 4,000,000, between 300,000 and 3,000,000, or between 400,000 and 2,500,000. The method for determining the weight-average molecular weight (Mw) will be described in detail later.

[0086] The glass transition temperature (Tg) of the acrylic polymer (A) is preferably below 0°C, but can be -100°C to 0°C, -100°C to -10°C, -100°C to -20°C, -100°C to -30°C, or -100°C to -40°C. The method for determining the glass transition temperature (Tg) will be detailed later.

[0087] Acrylic polymers (A) are typically obtained by polymerizing monomer components (Ma).

[0088] The monomer component (Ma) preferably contains an alkyl (meth)acrylate (m1) having an alkyl group having 1 to 14 carbon atoms as the ester moiety. The alkyl (meth)acrylate (m1) may be a single type or two or more types.

[0089] Examples of alkyl methacrylates (m1) include: methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, isooctyl methacrylate, n-nonyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, n-dodecyl methacrylate, n-tridecyl methacrylate, and n-tetradecyl methacrylate. Among them, alkyl esters of (meth)acrylate having an alkyl group having 6 to 14 carbon atoms as the ester moiety are preferred, and examples include: (meth)acrylate hexyl ester, (meth)acrylate-2-ethylhexyl ester, (meth)acrylate n-octyl ester, (meth)acrylate isooctyl ester, (meth)acrylate n-nonyl ester, (meth)acrylate isononyl ester, (meth)acrylate n-decyl ester, (meth)acrylate isodecyl ester, (meth)acrylate n-dodecyl ester, (meth)acrylate n-tridecyl ester, (meth)acrylate n-tetradecyl ester.

[0090] The content of alkyl methacrylate (m1) in the monomer component (Ma) is, for example, 50% by weight or more, or 50% to 99% by weight, or 60% to 99% by weight, or 70% to 98% by weight, or 80% to 98% by weight.

[0091] The monomer component (Ma) may contain hydroxyl-containing monomers (m2). There may be only one hydroxyl-containing monomer (m2) or two or more.

[0092] Examples of hydroxyl-containing monomers (m2) include: 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, etc.; polypropylene glycol mono(meth)acrylate; and N-hydroxyethyl(meth)acrylamide.

[0093] The proportion of hydroxyl-containing monomers (m2) in the monomer component (Ma) is, for example, less than 30% by weight, or can be 0.1% to 30% by weight, or 1% to 20% by weight, or 2% to 15% by weight, or 2.5% to 10% by weight, or 3% to 5% by weight.

[0094] The monomer component (Ma) may contain a carboxyl-containing monomer (m3). The carboxyl-containing monomer (m3) may be only one type or may be two or more types.

[0095] Examples of carboxyl-containing monomers (m3) include: (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their anhydrides (such as maleic anhydride, itaconic anhydride, and other anhydride-containing monomers), with (meth)acrylic acid being a representative example.

[0096] The proportion of carboxyl-containing monomers (m3) in the monomer component (Ma) can be any suitable proportion without impairing the effects of the present invention. For example, the proportion of carboxyl-containing monomers (m3) in the monomer component (Ma) can be 30% by weight or less, or it can be 0% to 25% by weight, or 0% to 20% by weight, or 0% to 15% by weight, or 0% to 12% by weight, or 0% to 10% by weight.

[0097] The monomer component (Ma) may contain any other suitable monomers without impairing the effects of the invention. There may be only one or more other monomers.

[0098] Other monomers include, for example: amide-containing monomers such as (meth)acrylamide and N,N-dimethyl(meth)acrylamide; amino-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; epoxy-containing monomers such as glycidyl (meth)acrylate and methylglycidyl (meth)acrylate; cyano-containing monomers such as acrylonitrile and methacrylonitrile; and N-vinyl-2-pyrrolidone, N-vinylpiperidone, N-vinylimidazolium, and vinyloxazone. Heterocyclic vinyl monomers such as azoles; monomers containing isocyanate groups such as 2-methacryloyloxyethyl isocyanate; (meth)acrylates with alicyclic hydrocarbon groups such as cyclopentyl methacrylate, cyclohexyl methacrylate, and isobornyl methacrylate; (meth)acrylates with aromatic hydrocarbon groups such as phenyl methacrylate, phenoxyethyl methacrylate, and benzyl methacrylate; and (meth)acrylate alkoxyalkyl esters such as 2-methoxyethyl methacrylate and 2-ethoxyethyl methacrylate.

[0099] Other monomers may also be multifunctional monomers. A multifunctional monomer is a monomer having two or more olefinic unsaturated groups in one molecule. Any suitable olefinic unsaturated group may be used as the olefinic unsaturated group without impairing the effects of the present invention. Examples of such olefinic unsaturated groups include free radical polymerizable functional groups such as vinyl, propenyl, isopropenyl, vinyl ether (ethoxy), and allyl ether (allyloxy). Examples of multifunctional monomers include: hexanediol di(meth)acrylate, butanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, allyl methacrylate, vinyl methacrylate, and urethane acrylate.

[0100] The proportion of other monomers in the monomer component (Ma) can be any suitable proportion without impairing the effects of the present invention. The proportion of other monomers in the monomer component (Ma) can be, for example, 50% by weight or less, or 0% to 50% by weight, or 0% to 30% by weight, or 0% to 20% by weight, or 0% to 10% by weight, or 0% to 5% by weight, or 0% to 1% by weight.

[0101] As a method for preparing acrylic polymer (A), various polymerization methods known as preparation methods for acrylic polymer (A) can be appropriately employed, such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization. Among these polymerization methods, solution polymerization is preferred. As a monomer supply method for solution polymerization, appropriate methods can be adopted, such as one-time loading of the entire monomer component, continuous supply (droplet addition), and batch supply (droplet addition). The polymerization temperature can be appropriately selected according to the type of monomer and solvent used, the type of polymerization initiator, etc., preferably 20℃ to 200℃, but can also be 30℃ to 170℃, 35℃ to 160℃, or 40℃ to 140℃. As a method for preparing acrylic polymer (A), active energy ray irradiation polymerization can be employed, such as photopolymerization by irradiation with UV light (typically carried out in the presence of a photopolymerization initiator); and radiation polymerization by irradiation with β-rays, γ-rays, etc.

[0102] As a solvent for solution polymerization (polymerization solvent), any suitable organic solvent can be appropriately selected. Examples include: aromatic compounds such as toluene (typically aromatic hydrocarbons); acetate esters such as ethyl acetate; and aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane.

[0103] The initiator used for polymerization (polymerization initiator) can be appropriately selected from any suitable polymerization initiator depending on the type of polymerization method. There can be only one polymerization initiator or two or more.

[0104] Examples of polymerization initiators include thermal polymerization initiators and photopolymerization initiators.

[0105] Thermal polymerization initiators are typically used when acrylic polymers (A) are obtained by solution polymerization. Examples of such thermal polymerization initiators include azo initiators such as 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, dimethyl 2,2'-azobis(2-methylpropionic acid) and 4,4'-azobis-4-cyanopentanoic acid.

[0106] The photopolymerization initiator is preferably used when obtaining the acrylic polymer (A) by polymerization with active energy rays. Examples of photopolymerization initiators include: benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-keto alcohol-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzoyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.

[0107] Examples of benzoin ether-based photopolymerization initiators include: benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, and benzoin isobutyl ether. Examples of acetophenone-based photopolymerization initiators include: 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, and 1-hydroxycyclohexylphenyl ketone. Examples of α-ketool-based photopolymerization initiators include: 2-methyl-2-hydroxyacetone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of benzoin-based photopolymerization initiators include benzoin. Examples of benzoyl-based photopolymerization initiators include benzoyl. Examples of benzophenone-based photopolymerization initiators include: benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenyl ketone. Examples of ketal-based photopolymerization initiators include benzoyladimethyl ketal.

[0108] The amount of polymerization initiator used can be any appropriate amount without impairing the effects of the present invention. The amount of polymerization initiator used relative to 100 parts by weight of the monomer component (Ma) can be, for example, 0.001 parts by weight to 10 parts by weight, 0.005 parts by weight to 5 parts by weight, 0.01 parts by weight to 3 parts by weight, or 0.05 parts by weight to 1 part by weight.

[0109] During polymerization, any other suitable additives may be added without impairing the effects of the present invention.

[0110] <1-3-b. Crosslinking agent> The acrylic adhesive composition (A) may contain a crosslinking agent. There may be only one type of crosslinking agent or two or more.

[0111] The crosslinking agent content in the acrylic adhesive composition (A) is preferably 0.1 to 30.0 parts by weight relative to 100 parts by weight of the acrylic polymer (A), and can be 0.5 to 20.0 parts by weight, 1.0 to 15.0 parts by weight, 1.5 to 10.0 parts by weight, or 2.0 to 8.0 parts by weight.

[0112] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, organosilicon-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl etherified melamine-based crosslinking agents, metal chelate-based crosslinking agents, and peroxides. From the perspective of further demonstrating the effects of the present invention, it is preferable to select at least one from the group consisting of isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and peroxides.

[0113] As an isocyanate-based crosslinking agent, compounds having two or more isocyanate groups in one molecule (including isocyanate regenerated polar groups whose isocyanate groups are temporarily protected by end-capping agents or polymerization) can be used. Examples of isocyanate-based crosslinking agents include toluene diisocyanate.

[0114] Examples of isocyanate-based crosslinking agents include: lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-toluene diisocyanate and 4,4'-diphenylmethane diisocyanate; isocyanate adducts such as trimethylolpropane / hexamethylene diisocyanate trimer adducts (e.g., manufactured by TOSOH, trade name: CORONATE HL) and isocyanurate derivatives of hexamethylene diisocyanate (e.g., manufactured by TOSOH, trade name: CORONATE HX); and trimethylolpropane adducts of phenylenediamine diisocyanate (e.g., manufactured by Mitsui Chemicals, trade name: TAKENATE). D110N), trimethylolpropane adducts of toluene diisocyanate (e.g., manufactured by Mitsui Chemicals, trade name: TAKENATE D101E); polyether polyisocyanates, polyester polyisocyanates, and their adducts with various polyols.

[0115] As an epoxy crosslinking agent, a polyfunctional epoxy compound having two or more epoxy groups in one molecule can be used. Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-phenylenediamine. Commercially available epoxy crosslinking agents include, for example, those manufactured by Mitsubishi Gas Chemical Co., Ltd. under the trade names "TETRAD-C" and "TETRAD-X".

[0116] Examples of peroxides include benzoyl peroxide, dicumyl peroxide, and di-tert-butyl peroxide. Commercially available peroxides include the "NYPER BMT" and "NYPER BW" series manufactured by Nippon Oils & Fats Co., Ltd.

[0117] <1-3-c. Other ingredients> The acrylic adhesive composition (A) may contain any other suitable ingredients without impairing the effects of the present invention. Examples of such other ingredients include, for instance: crosslinking catalysts, crosslinking promoters, crosslinking delay agents, surfactants, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenolic resins, etc.), anti-aging agents, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, nucleating agents, chain transfer agents, plasticizers, softeners, antistatic agents (ionic compounds, etc.), conductive agents, stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, etc.

[0118] The content of other components in the acrylic adhesive composition (A) can be any appropriate amount without impairing the effects of the present invention. The content of other components in the acrylic adhesive composition (A) relative to 100 parts by weight of the acrylic polymer (A) can be, for example, 0 parts by weight to 30 parts by weight, 0 parts by weight to 20 parts by weight, 0 parts by weight to 10 parts by weight, or 0 parts by weight to 5 parts by weight.

[0119] 1-4. Peeling the Liner In the carrier film of the embodiments of the present invention, a release liner may be provided on the exposed side of the adhesive layer (the side opposite to the substrate) until use.

[0120] Examples of release liner materials include: release liner materials with silicone treatment on the surface of a substrate such as paper or plastic film (liner substrate); release liner materials with long-chain alkyl groups treated on the surface of a substrate such as paper or plastic film (liner substrate); and release liner materials laminated on the surface of a substrate such as paper or plastic film (liner substrate) using polyolefin resins. Examples of plastic films used as liner substrates include: polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, and ethylene-vinyl acetate copolymer film.

[0121] The thickness of the release liner is preferably 1μm to 500μm, but can be 3μm to 450μm, 5μm to 400μm, or 10μm to 300μm.

[0122] 2. Reinforcing Membranes with Carrier Membranes In the case of the reinforcing film with a carrier film according to embodiments of the present invention, a reinforcing film is provided on the adhesive layer side of the carrier film according to embodiments of the present invention. The reinforcing film typically includes a substrate and an adhesive layer.

[0123] In the reinforcing film with a carrier film according to embodiments of the present invention, as long as there is one or more reinforcing films on the adhesive side of the carrier film, any appropriate number can be used without impairing the effects of the present invention. The number of such reinforcing films can be, for example, one to ten, one to five, or one to three.

[0124] A schematic cross-sectional view of a reinforced membrane with a carrier membrane according to one embodiment of the present invention is shown in Figure 2 . Figure 2 This is an embodiment in which two reinforcing membranes are arranged in a manner with gaps between them on a carrier membrane. Figure 2 In the reinforced film 3000 with a carrier film shown, a reinforcing film 2000A and a reinforcing film 2000B are disposed in a carrier film 1000 with a gap L. The carrier film 1000 includes an antistatic layer 100, a substrate 200, and an adhesive layer 300. The reinforcing film 2000A includes a substrate 10A and an adhesive layer 20A. The reinforcing film 2000B includes a substrate 10B and an adhesive layer 20B. On the exposed side of the adhesive layer 20A of the reinforcing film 2000A and the exposed side of the adhesive layer 20B of the reinforcing film 2000B, as shown... Figure 2 As shown, a common peeling gasket 4000 can be set. The above interval L only needs to be greater than 0 mm, and can be 0.1 mm to 5.0 mm, 0.2 mm to 3.0 mm, 0.3 mm to 2.0 mm, 0.5 mm to 1.5 mm, or 0.7 mm to 1.5 mm.

[0125] The reinforcing film with a carrier film in embodiments of the present invention may have any suitable other layers without impairing the effects of the present invention. These other layers may be only one type or two or more. Examples of such other layers include, for instance, a release liner disposed on the exposed surface of the adhesive layer of the reinforcing film, and an antistatic layer disposed on at least one side of the substrate of the reinforcing film.

[0126] The reinforcing film with a carrier film according to embodiments of the present invention can be manufactured by any suitable method without impairing the effects of the present invention. For example, one method for bonding the adhesive layer of the carrier film according to embodiments of the present invention to the substrate side of the reinforcing film can be described.

[0127] As a reinforcing film, it is generally possible to use a reinforcing film that is pre-attached to the exposed side of an optical component, electronic component, etc., during the manufacture of optical devices, electronic components, etc., in order to impart rigidity and impact resistance to the optical component, electronic component, etc. The reinforcing film typically has a substrate and an adhesive layer. Any suitable reinforcing film can be used as the reinforcing film without impairing the effects of the present invention. For example, known reinforcing films can be used (e.g., Japanese Patent No. 7511678, Japanese Unexamined Patent Application Publication No. 2023-131574, Japanese Unexamined Patent Application Publication No. 2023-131575).

[0128] As a substrate that can be used for reinforcing films, the description of the substrate mentioned in Section 1-2, "Substrate", can be cited. On at least one side of the substrate that can be used for reinforcing films, an arbitrary and suitable antistatic layer can be provided for purposes such as suppressing static electricity generation. The antistatic layer can be one layer or two or more layers. For example, the antistatic layer described in Patent Document 2 can be cited as such an antistatic layer.

[0129] The reinforcing film may have one or more adhesive layers. As the adhesive layer of the reinforcing film, any suitable adhesive can be used without impairing the effects of the present invention. Examples of adhesives constituting the adhesive layer include acrylic adhesives, urethane adhesives, rubber adhesives, and silicone adhesives. As the adhesive, it can be appropriately selected from various conventionally known adhesives without impairing the effects of the present invention.

[0130] A representative embodiment of the adhesive is an acrylic adhesive. Hereinafter, an embodiment of an acrylic adhesive will be briefly described. Of course, the acrylic adhesive described below is not limited to the adhesive layer that can constitute the reinforcing film.

[0131] The acrylic adhesive is formed from the acrylic adhesive composition (B). The acrylic adhesive can be formed by crosslinking the acrylic adhesive composition (B) through heating, ultraviolet irradiation, or other means. When the acrylic adhesive is formed from the acrylic adhesive composition (B), any suitable method can be used to form the acrylic adhesive without impairing the effects of the present invention. For example, the description mentioned in section <1-3-a. Acrylic Polymer (A)> can be cited as a method for forming such an acrylic adhesive.

[0132] The acrylic adhesive composition (B) comprises an acrylic polymer (B) as a base polymer. The acrylic polymer (B) may be one or more. Regarding the weight-average molecular weight of the acrylic polymer (B), for example, the description mentioned in section <1-3-a. Acrylic Polymer (A)> can be cited.

[0133] Regarding the proportion of acrylic polymer (B) in the acrylic adhesive composition (B), the description mentioned in section <1-3-a. Acrylic polymer (A)> can be cited, for example.

[0134] As an acrylic polymer (B), it can be obtained, for example, by polymerizing a monomer component (Mb) comprising: an alkyl (meth)acrylate (m4) having an alkyl group having 4 to 12 carbon atoms as the ester moiety; and at least one selected from the group consisting of a hydroxyl-containing monomer (m2) and a carboxyl-containing monomer (m3). The content of the alkyl (meth)acrylate (m4) in the monomer component (Mb) is, for example, 10% to 99% by weight. The content of at least one selected from the group consisting of a hydroxyl-containing monomer (m2) and a carboxyl-containing monomer (m3) in the monomer component (Mb) is, for example, 0.1% to 30% by weight. The alkyl (meth)acrylate (m4) can be one type or two or more types. Examples of alkyl (meth)acrylate (m4) include, for example, n-butyl acrylate and 2-ethylhexyl acrylate.

[0135] The monomer component (Mb) may contain any suitable other monomers without impairing the effects of the invention. There may be only one other monomer or two or more. The content of other monomers in the monomer component (Mb) may be, for example, 0% to 20% by weight.

[0136] As a method for preparing acrylic polymers (B), the description mentioned in section <1-3-a. Acrylic polymers (A)> can be cited, for example.

[0137] The acrylic adhesive composition (B) may contain a crosslinking agent. There may be only one crosslinking agent or two or more. For example, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and peroxides mentioned in section <1-3-b. Crosslinking Agents> can be cited as crosslinking agents. The content of the crosslinking agent in the acrylic adhesive composition (B) is, for example, 0.005 parts by weight to 20 parts by weight relative to 100 parts by weight of the acrylic polymer (B).

[0138] The acrylic adhesive composition (B) may contain acrylic oligomers. There may be only one type of acrylic oligomer or two or more. The proportion of the acrylic oligomers in the acrylic adhesive composition (B) relative to the solid components (100 parts by weight) of the acrylic polymer (B) may be, for example, 0 to 50 parts by weight, 0 to 40 parts by weight, or 0 to 30 parts by weight.

[0139] The weight-average molecular weight of acrylic oligomers can range from 1,000 to 30,000, or even from 1,000 to 20,000, 1,500 to 10,000, or 2,000 to 8,000. It should be noted that the weight-average molecular weight (Mw) can be calculated using the GPC method based on polystyrene.

[0140] As acrylic oligomers, acrylic oligomers obtained from monomers having an intramolecularly cyclic (meth)acrylate as an essential component are preferred. The intramolecularly cyclic (meth)acrylate can be a single type or two or more types. Specifically, examples of intramolecularly cyclic (meth)acrylates include: cyclohexyl acrylate, cyclohexyl methacrylate, dicyclopentyl acrylate, and dicyclopentyl methacrylate.

[0141] The proportion of (meth)acrylates with intramolecular cyclic structures relative to the total amount of monomer components constituting acrylic oligomers is, for example, 50% to 100% by weight, 70% to 99% by weight, 80% to 98% by weight, 90% to 97% by weight, or 92% to 97% by weight.

[0142] The monomer components constituting acrylic oligomers may include carboxyl-containing monomers (m3). As such carboxyl-containing monomers (m3), the description mentioned in section <1-3-a. Acrylic Polymers (A)> can be cited, for example.

[0143] The proportion of carboxyl-containing monomers relative to the total amount of monomer components constituting acrylic oligomers is, for example, 0% to 20% by weight, 1% to 10% by weight, 2% to 9% by weight, 3% to 8% by weight, or 4% to 7% by weight.

[0144] The monomeric components constituting the acrylic oligomer may include any suitable other monomers without impairing the effects of the present invention. There may be only one or more other monomers. The proportion of other monomers relative to the total amount of monomeric components constituting the acrylic oligomer is, for example, 0% to 20% by weight.

[0145] As acrylic oligomers, they are preferably formed by polymerization of a composition comprising a monomeric component, the essential component of which is an intramolecularly cyclic (meth)acrylate. Such compositions may contain any suitable other components besides the monomeric component. Examples of such other components include, for instance, polymerization initiators, chain transfer agents, and solvents. The descriptions of polymerization initiators, chain transfer agents, and solvents can be found in section <1-3-a. Acrylic Polymers (A)>.

[0146] Acrylic oligomers can be prepared by any suitable polymerization method without compromising the effects of the present invention.

[0147] The acrylic adhesive composition (B) may contain any suitable other components without impairing the effects of the invention. The proportion of these other components in the acrylic adhesive composition (B) relative to the solid components (100 parts by weight) of the acrylic polymer (B) is, for example, 0% to 20% by weight.

[0148] [Example] The present invention will now be specifically described through examples, but the present invention is not limited to these examples in any way. It should be noted that the testing and evaluation methods in the examples are as follows. It should be noted that when "parts" are used, they refer to "parts by weight" unless otherwise specified; and when "%" are used, they refer to "% by weight" unless otherwise specified.

[0149] <Determination of weight-average molecular weight (Mw) of acrylic polymers> The weight-average molecular weight (Mw) of acrylic polymers was determined by gel permeation chromatography (GPC). Specifically, an Alliance (Waters Corporation) was used as the GPC apparatus. Considering the polymer concentration of the sample, a 0.1 wt% tetrahydrofuran solution was prepared, allowed to stand for 20 hours, filtered through a 0.45 μm membrane filter, and the resulting filtrate was then subjected to GPC analysis. The GPC analysis conditions were as follows.

[0150] • Sample concentration: 0.1% by weight (tetrahydrofuran solution).

[0151] • Sample injection volume: 30 μL.

[0152] • Chromatographic column: Trade name "TSKgel SuperHZM-H" (manufactured by TOSOH).

[0153] • Eluent: Tetrahydrofuran.

[0154] • Flow rate: 0.2 mL / min.

[0155] • Detector: Differential refractometer (RI).

[0156] • Column temperature (measurement temperature): 40℃.

[0157] • Standard sample: polystyrene (PS).

[0158] <Determination of the weight-average molecular weight (Mw) of acrylic oligomers> The weight-average molecular weight (Mw) of acrylic oligomers was determined by gel permeation chromatography (GPC). Specifically, an HLC-8320GPC (manufactured by TOSOH) was used as the GPC measuring instrument. Considering the polymer concentration of the sample, a 0.1% by weight tetrahydrofuran solution was prepared, allowed to stand for 20 hours, filtered through a 0.45 μm membrane filter, and the resulting filtrate was then subjected to GPC determination. The GPC determination conditions are as follows.

[0159] • Sample concentration: 0.1% by weight (tetrahydrofuran solution).

[0160] • Sample injection volume: 100 μL.

[0161] • Chromatographic column: Trade name "TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000" (manufactured by TOSOH).

[0162] • Eluent: Tetrahydrofuran.

[0163] • Flow rate: 0.6 mL / min.

[0164] • Detector: Differential refractometer (RI).

[0165] • Column temperature (measurement temperature): 40℃.

[0166] • Standard sample: polystyrene (PS).

[0167] <Glass transition temperature Tg> The glass transition temperature (Tg) of acrylic polymers is calculated using the Fox formula based on the Tgi of the homopolymer of each monomer i constituting the polymer and the weight fraction (weight-based copolymerization ratio) Wi of monomer i. The Fox formula, shown below, is the relationship between the Tg of the copolymer and the glass transition temperature (Tgi) of the homopolymer formed by homopolymerizing each monomer i constituting the copolymer.

[0168] 1 / Tg = Σ(Wi / Tgi) In the Fox formula above, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (weight-based copolymerization ratio), and Tgi represents the glass transition temperature of the homopolymer of each monomer i (unit: K).

[0169] The Tg of a homopolymer, which is a homopolymer of various monomers, can be, for example, the following values.

[0170] 2-Ethylhexyl acrylate (2EHA): -70℃.

[0171] 2-Hydroxyethyl acrylate (HEA): -15℃.

[0172] 4-Hydroxybutyl acrylate (4HBA): -32℃.

[0173] n-Butyl acrylate (BA): -55℃.

[0174] Acrylic acid (AA): 106℃.

[0175] Methyl methacrylate (MMA): 105℃.

[0176] Dicyclopentyl methacrylate (DCPMA): 175℃.

[0177] Cyclohexyl methacrylate (CHMA): 66℃.

[0178] For the Tg of homopolymers of various monomers, and for homopolymers of monomers other than those mentioned above, values ​​recorded in publicly available sources can be used, such as those recorded in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). If multiple values ​​are recorded in the "Polymer Handbook," the conventional value should be used. For monomers not recorded in the "Polymer Handbook," the values ​​listed in the monomer manufacturer's catalog should be used. For homopolymers of monomers not recorded in the "Polymer Handbook" and for which no monomer manufacturer's catalog value is provided, the Tg value obtained using the measurement method described in Japanese Patent Application Publication No. 2007-51271 should be used.

[0179] <Pick-up rating> Peel off the release liner from the carrier film with the antistatic layer, and apply the exposed adhesive layer to the glass plate (soda-lime glass, Matsunami Glass Industry Co., Ltd.) with a 15μm thick double-sided adhesive tape (made by Nitto Denko, trade name "No.7"), and then apply it back and forth once with a 2kg hand roller.

[0180] Next, adhesive tape (manufactured by Nitto Denko Corporation, trade name "No. 31 tape") was applied to the surface of the antistatic layer (upper surface) of the obtained evaluation sample by pressing it back and forth once with a 2kg hand roller.

[0181] Then, place it at 23°C for 30 minutes as an evaluation sample.

[0182] For the obtained evaluation specimens, the load when No. 31 tape was peeled from the surface of the antistatic layer was measured, and the average load at this time was determined using a tensile testing machine. The tensile testing machine used was the Shimadzu Autograph AG-Xplus HS 6000mm / min high-speed mode (AG-50NX plus) manufactured by Shimadzu Corporation. The tensile test conditions were set as follows: peel angle: 180 degrees, peel speed (tensile speed): 300mm / min.

[0183] The higher the measured peel force value, the better the adhesion to the pickup tape, which means that it can demonstrate good pickup performance.

[0184] <Determination of Surface Resistivity> In an atmosphere of 23°C and 50% RH, using a surface resistivity meter (MODEL152) (manufactured by TREK), with an applied voltage of 10V, the probe (152P-2P) was pressed against the surface of the antistatic layer for 10 seconds, and the displayed value was read. It should be noted that in Table 1, values ​​such as XE+Y refer to X×10⁻¹⁰. Y .

[0185] [Manufacturing Example 1]: Manufacturing of acrylic polymer (A) for carrier membranes In a reaction vessel equipped with a thermometer, stirrer, reflux condenser, and nitrogen inlet, 200 parts by weight of 2-ethylhexyl acrylate (2EHA) and 8 parts by weight of 2-hydroxyethyl acrylate (HEA) were added as monomers; 0.4 parts by weight of azobisisobutyronitrile (AIBN) as a polymerization initiator; and 312 parts by weight of ethyl acetate as a solvent. Nitrogen gas was introduced while the mixture was slowly stirred, and the liquid temperature in the flask was maintained at approximately 65°C for 6 hours to produce a solution of acrylic polymer (A) (solid content 40% by weight). The obtained acrylic polymer (A) had a weight-average molecular weight of 540,000 and a glass transition temperature (Tg) of -68°C.

[0186] [Manufacturing Example 2]: Manufacturing of acrylic adhesive composition (A) for carrier film A solution of the acrylic polymer (A) obtained in Manufacturing Example 1 (solid content 40% by weight) was diluted to 20% by weight with ethyl acetate. Relative to the solid content of the solution (100 parts by weight), 0.3 parts by weight of polyoxyethylene-1-(allyloxymethyl)alkyl ether ammonium sulfate (trade name "AQUALON KH-10", manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.) as a surfactant, 5 parts by weight of isocyanurate derivative of hexamethylene diisocyanate (trade name "CORONATEHX", manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent, and 0.03 parts by weight of dioctyltin dilaurate (trade name "OL-1", manufactured by Tokyo Fine Chemical Co., Ltd.) as a crosslinking catalyst were added. Furthermore, 3 parts by weight of acetylacetone were added relative to the total solvent volume as a crosslinking delay agent. The mixture was then stirred to produce the acrylic adhesive composition (A).

[0187] [Manufacturing Example 3]: Manufacturing of acrylic polymer (B) for reinforcing films In a reaction vessel equipped with a thermometer, stirrer, reflux cooling pipe, and nitrogen inlet pipe, 95 parts by weight of butyl acrylate (BA) and 5 parts by weight of acrylic acid (AA) as monomers, 0.2 parts by weight of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, and 233 parts by weight of ethyl acetate as a solvent were added. Nitrogen gas was introduced, and nitrogen replacement was carried out for about 1 hour with stirring. Then, the mixture was heated to 60°C and reacted for 7 hours to obtain a solution of acrylic polymer (B) with a weight average molecular weight of 600,000.

[0188] [Manufacturing Example 4]: Manufacturing of acrylic oligomers for reinforcing films In a reaction vessel equipped with a thermometer, stirrer, reflux cooling pipe, and nitrogen inlet pipe, 95 parts by weight of cyclohexyl methacrylate (CHMA) and 5 parts by weight of acrylic acid (AA) were added as monomers; 3 parts by weight of 2-mercaptoethanol as a chain transfer agent; 0.2 parts by weight of azobisisobutyronitrile (AIBN) as a polymerization initiator; and 103.2 parts by weight of toluene as a solvent. Nitrogen gas was introduced while stirring for 1 hour. After removing oxygen from the polymerization system, the temperature was raised to 70°C and the reaction was carried out for 3 hours, followed by a further reaction at 75°C for 2 hours to obtain a solution of acrylic oligomers with a weight average molecular weight of 4000 (50% by weight solids).

[0189] [Manufacturing Example 5]: Manufacturing of acrylic adhesive composition (B) for reinforcing films An acrylic adhesive composition (B) was prepared by adding 0.075 parts by weight of a tetrafunctional epoxy compound (manufactured by Mitsubishi Gas Chemical, trade name "TETRAD-C") as a crosslinking agent and 25 parts by weight of an acrylic oligomer obtained in Manufacturing Example 4 as solid components to a solution of the acrylic polymer (B) obtained in Manufacturing Example 3.

[0190] [Manufacturing Example 6]: Manufacturing of a reinforcing film with a release liner 100 parts by weight of polyester resin “VYLONAL MD-1480” (25% aqueous solution, manufactured by Toyobo Co., Ltd.) as an adhesive (based on solids), 20 parts by weight of aqueous solution “Baytron P” (manufactured by HCStarck Co., Ltd.) containing 0.5% poly(3,4-ethylenedioxythiophene) (PEDOT) and 0.8% polystyrene sulfonic acid (weight average molecular weight Mw = 150,000) (PSS) as an antistatic agent (based on solids), and 5 parts by weight of melamine-based crosslinking agent (trade name “SUMIMAL M-50W”, manufactured by Sumitomo Chemical Co., Ltd.) as a crosslinking agent (based on solids) were added to a water / ethanol mixed solvent (water / ethanol ratio = 1 / 1) and stirred for about 20 minutes to mix thoroughly. Thus, an antistatic layer forming composition (2) with an NV of about 0.4% was prepared.

[0191] On one side of a 75 μm thick polyethylene terephthalate film serving as a substrate, the aforementioned antistatic layer forming composition (2) was coated using a bar coater. After drying at 130°C for 1 minute, a transparent antistatic layer with a thickness of 30 nm was formed on one side of the substrate. Next, on the side of the substrate without the antistatic layer, the acrylic adhesive composition (B) obtained in Manufacturing Example 5 was coated using a feed roller. After heating at 130°C for 60 seconds, an adhesive layer with a thickness of 13 μm was formed. Then, a release liner (a 75 μm thick polyethylene terephthalate film with silicone release treatment on one side) was bonded to the coated surface of the adhesive layer, thus creating a reinforcing film with a release liner, consisting of a release liner (75 μm thickness), an adhesive layer (13 μm thickness), a substrate (75 μm thickness), and an antistatic layer (30 nm thickness).

[0192] [Example 1] <Preparation of Composition (1) for Antistatic Layer Formation> 50 parts by weight of the polyester resin “VYLONAL MD-1480” (25% aqueous solution, manufactured by Toyobo Co., Ltd.) as an adhesive (by solids), 50 parts by weight of the aqueous solution “Baytron P” (manufactured by HCStarck Co., Ltd.) containing 0.5% poly(3,4-ethylenedioxythiophene) (PEDOT) and 0.8% polystyrene sulfonic acid (PSS) as an antistatic agent (by solids), 20 parts by weight of the melamine-based crosslinking agent (trade name “SUMIMAL M-50W”, manufactured by Sumitomo Chemical Co., Ltd.) as a crosslinking agent (by solids), and 10 parts by weight of the water-based polyurethane resin with an ether structure (trade name “TAKELAC W-6061”, manufactured by Mitsui Chemicals Co., Ltd.) as a solids, were added to a water / ethanol mixed solvent (water / ethanol weight ratio = 50 / 50), stirred for about 20 minutes, and thoroughly mixed. Thus, an antistatic layer forming composition (1) with an NV of about 0.35% was prepared.

[0193] <Manufacturing of carrier membrane (1)> On one side of a 75 μm thick polyethylene terephthalate film serving as a substrate, the aforementioned antistatic layer forming composition (1) was coated using a bar coater and dried at 130°C for 1 minute, thus forming a 30 nm thick transparent antistatic layer on one side of the substrate. Next, on the side of the substrate without the antistatic layer, the acrylic adhesive composition (A) obtained in Manufacturing Example 2 was coated using a feed roller and dried at 130°C for 30 seconds, forming an adhesive layer with a thickness of 5 μm. Next, a release liner (a 50 μm thick polyethylene terephthalate film with silicone release treatment on one side) was bonded to the coated surface of the adhesive layer, thus creating a carrier film (1) with a release liner, consisting of a release liner (50 μm thick), an adhesive layer (5 μm thick), a substrate (75 μm thick), and an antistatic layer (30 nm thick).

[0194] The pickability evaluation and surface resistivity of the obtained carrier membrane with release liner (1) were performed.

[0195] The results are shown in Table 1.

[0196] <Manufacturing of the reinforced membrane (1) with a carrier membrane> The reinforcing film with a release liner obtained in Manufacturing Example 6 was cut into lengthwise 134mm × widthwise 70mm pieces to serve as the first reinforcing film with a release liner.

[0197] The reinforcing film with a release liner obtained in Manufacturing Example 6 was cut into lengthwise 15mm × widthwise 70mm pieces to serve as a second reinforcing film with a release liner.

[0198] On a release liner measuring 150mm in length and 70mm in width (a 25μm thick polyethylene terephthalate film with silicone release treatment on one side), the aforementioned first reinforcing film with a release liner and the aforementioned second reinforcing film with a release liner are bonded together with their respective longitudinal and transverse directions parallel, and with a 1mm gap between the transverse edges of the first and second reinforcing films, so that the adhesive layer of each reinforcing film with a release liner forms the release liner side. It should be noted that the release liner of each reinforcing film with a release liner is peeled off before bonding.

[0199] Next, the carrier film (1) with release liner obtained above is cut into a size of 150mm in length and 70mm in width. The release liner is peeled off so that it overlaps exactly with the release liner of the size of 150mm in length and 70mm in width when viewed from the plane, and is attached to the substrate side of each reinforcing film.

[0200] As described above, a reinforced membrane with a carrier membrane (1) is obtained.

[0201] [Examples 2-4] As shown in Table 1, except that the amount of the formulation of the water-based polyurethane resin with an ether structure, "TAKELAC W-6061" (manufactured by Mitsui Chemicals Co., Ltd.), was changed to 15 parts by weight, 20 parts by weight, and 30 parts by weight in terms of solid content, was carried out in the same manner as in Example 1, and antistatic layer forming compositions (2) to (4), carrier films (2) to (4), and reinforcing films (2) to (4) with carrier films were obtained.

[0202] The results are shown in Table 1.

[0203] [Examples 5-8] As shown in Table 1, instead of the trade name "TAKELAC W-6061" (manufactured by Mitsui Chemicals Co., Ltd.), which is a water-based polyurethane resin with an ether structure, 10 parts by weight of solid content were prepared, and 10 parts by weight, 15 parts by weight, 20 parts by weight, and 30 parts by weight of the trade name "SUPERFLEX SF-870" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.), which is a water-based polyurethane resin with an ether structure, were prepared. Otherwise, the same procedure as in Example 1 was followed to obtain the antistatic layer forming composition (5) to (8), the carrier film (5) to (8), and the reinforcing film (5) to (8) with the carrier film.

[0204] The results are shown in Table 1.

[0205] [Examples 9-12] As shown in Table 1, instead of the trade name "TAKELAC W-6061" (manufactured by Mitsui Chemicals Co., Ltd.), which is a water-based polyurethane resin with an ether structure, 10 parts by weight of solids were replaced with 10 parts by weight, 15 parts by weight, 20 parts by weight, and 30 parts by weight of the trade name "TAKELAC WS-5984" (manufactured by Mitsui Chemicals Co., Ltd.), which is a water-based polyurethane resin with an ester structure. Otherwise, the same procedure as in Example 1 was followed to obtain antistatic layer forming compositions (9) to (12), carrier films (9) to (12), and reinforcing films (9) to (12) with carrier films.

[0206] The results are shown in Table 1.

[0207] [Comparative Examples 1-4] As shown in Table 1, instead of the trade name "TAKELAC W-6061" (manufactured by Mitsui Chemicals Co., Ltd.), which is a water-based polyurethane resin with an ether structure, 10 parts by weight of solids were replaced with 10 parts by weight, 15 parts by weight, 20 parts by weight, and 30 parts by weight of the trade name "SUPERFLEX SF-460" (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.), which is a water-based polyurethane resin with a carbonate structure. Otherwise, the same procedure as in Example 1 was followed to obtain antistatic layer forming compositions (C1) to (C4), carrier films (C1) to (C4), and reinforcing films (C1) to (C4) with carrier films.

[0208] The results are shown in Table 1.

[0209] [Comparative Example 5] As shown in Table 1, except that water-based polyurethane resin was not used, the process was carried out in the same manner as in Example 1 to obtain an antistatic layer forming composition (C5), a carrier film (C5), and a reinforcing film with a carrier film (C5).

[0210] The results are shown in Table 1. Industrial availability The carrier film in the embodiments of the present invention is preferably used as a reinforcing film with a carrier film, for example, for reinforcing optical components, electronic components, etc.

Claims

1. A carrier film comprising, in sequence, an antistatic layer, a substrate, and an adhesive layer, The antistatic layer is formed from an antistatic layer forming composition comprising an adhesive and an antistatic agent. The composition for forming the antistatic layer comprises an aqueous polyurethane resin A, wherein the aqueous polyurethane resin A has at least one selected from the group consisting of an ether structure and an ester structure.

2. The carrier membrane according to claim 1, wherein, The content of the aqueous polyurethane resin A in the composition for forming the antistatic layer, calculated on a solids basis, is 1 to 50 parts by weight relative to a total of 100 parts by weight of the adhesive and the antistatic agent.

3. The carrier membrane according to claim 1, wherein, The adhesive is polyester resin.

4. The carrier membrane according to claim 1, wherein, The antistatic agent is a conductive polymer.

5. A reinforcing membrane with a carrier membrane, having a reinforcing membrane on the adhesive layer side of the carrier membrane as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Reinforcement film

    JP2023131574A

  • Reinforcement film

    JP2023131575A